Interconnectedness, Democratic Rights and Intelligence – An Uneasy International Relation (Journal of Governance and Development (JGD), 2014)
Our fundamental democratic rights originate from a pre-internet era and despite our changing world, legislation and international cooperation continues to lag, becoming increasingly irrelevant. The online threat environment remains severe and is becoming increasingly hostile, therefore analyzing the capabilities of our governments, of malicious actors and criminal entities are all pivotal in redeï¬ ning the role of law enforcement, intelligence and democratic rights online. This paper concludes that democratic rights and intelligence collection capabilities require reconsideration in the face of heightened online discourse and interaction. States do require the capacity and have the responsibility to protect electronic systems, however determining to what extent, controlled by what safeguards and administered by whom, will prove a grueling international process. It is inevitable that intelligence collection via electronic means will signiï¬ cantly increase over the coming years, therefore thoroughly analyzing individual democratic rights, assessing their continued relevance, reconsidering their implementation and implementing appropriate amendments and safeguards is a dialogue the international community needs to engage in.